An easy target: studentification, crime and safety of students in Johannesburg. Issue 3 (3rd July 2022) - Gregory, James
ABSTRACT: The socio-economic impacts associated with studentification are diverse. International and local research suggests that the process of studentification and growth of private student accommodation can attract certain types of crime to neighbourhoods that have a high concentration of students. Johannesburg is a popular city amongst local and regional students and attracts several thousand students each year. Some neighbourhoods have become popular student districts, providing student accommodation and spaces for student consumption. Drawing on several focus groups, netnography, and semi-structured interviews this paper explores the lived experiences of students and residents impacted by crime in studentified neighbourhoods. The findings of this paper suggest that students are exposed to certain types of targeted crime that impact their safety and wellbeing in Johannesburg. In addition, it was found that the impact of crime varies significantly according to the type of student accommodation and its location.